Comparing Voice Self-Assessment with Auditory Perceptual Analysis in Patients with Multiple Sclerosis - Bauer, Vladimir; Aleric, Zorica; Jancic, Ervin (International Archives of Otorhinolaryngology, 2015)
Introduction Disordered voice quality could be a symptom of multiple sclerosis (MS). The impact of MS on voice-related quality of life is still controversial.Objectives The aim of this study was to compare the results of voice self-assessment with the results of expert perceptual assessment in patients with MS.Methods The research included 38 patients with relapse-remitting MS (23 women and 15 men; ages 21 to 83, mean = 44). All participants filled out a Voice Handicap Index (VHI), and their voice sample was analyzed by speech and language professionals using the Grade Roughness Breathiness Asthenia Strain scale (GRBAS).Results The patients with MS had significantly higher VHI than control group participants (mean value 16.68 ± 16.2 compared with 5.29 ± 5.5, p = 0.0001). The study established a notable level of dysphonia in 55%, roughness and breathiness in 66%, asthenia in 34%, and strain in 55% of the vocal samples. A significant correlation was established between VHI and GRBAS scores (r = 0.3693, p = 0.0225), and VHI and asthenia and strain components (r = 0.4037 and 0.3775, p = 0.012 and 0.0195, respectively). The female group showed positive and significant correlation between claims for self-assessing one's voice (pVHI) and overall GRBAS scores, and between pVHI and grade, roughness, asthenia, and strain components. No significant correlation was found for male patients (p > 0.05).Conclusion A significant number of patients with MS experienced voice problems. The VHI is a good and effective tool to assess patient self-perception of voice quality, but it may not reflect the severity of dysphonia as perceived by voice and speech professionals.
Keywords: multiple sclerosis; quality of life; voice quality; voice disorders